Inflammatory pseudotumor: a 20‑Year single institutional experience (2020)
Background: Inflammatory pseudotumor (IPT) is a relatively rare benign disease. The aim of the study was to demonstrate the demographic distribution, clinical presentation, and histomorphological characteristics of IPT while highlighting its associated diagnostic challenges. Materials and Methods: A retrospective cross sectional review of all the IPT diagnosed in our institution between January 1999 and December 2018 was conducted. The samples were received from within and outside the hospital facility. The demographic data, clinical history, and histologic reports were reviewed. Results: A total of 25 cases of histologically confirmed IPT were seen. Patients’ age ranges from 7 to 74 years with a mean age of 38.96 years and standard deviation ± 17.94 years. There was a bimodal peak occurrence in the third and fifth decades. Most of the patients were adults (23, 92%), whereas only 2 (8%) were children. There was a female preponderance with a male to female ratio of 1:2.6. The head and neck had the highest number of cases (44%), followed by the gastrointestinal tract (GIT) (40%). Eight (73%) of head and neck cases occurred in the orbit. The presenting complaints depended on the site of the lesion with pain and swelling being the commonest symptoms irrespective of the site of the lesions. Two cases of bilateral IPT were observed. Immunohistochemistry was used in a certain condition of diagnostic dilemma. Conclusion: This study showed a female preponderance of IPT with the head and neck and GIT being the most common location. It is important to rule out other differentials in the diagnosis of IPT.